Effect of minimum quantity lubrication during micro-machining - Chen, Lixin (2011)
Micro-machining has become one of the most successful and latest developments in precision engineering. There are many types of micro-machining in the manufacturing industries, and the main focus in this project will be on micro-turning. During machining operation, heat and friction often generate between tools and chip in the cutting area, resulting in poor machining performance. Micro-machining operation is thus often more efficient with the use of lubrication or coolant. However, in the machining industries, coolants and lubricants are used in high quantities to reduce the temperature & friction at the cutting area. As a result, coolant in wet machining operations is a crucial economic issue. Therefore the interest has been switch to another alternative, machining with Minimum Quantity Lubricant (MQL), is gaining acceptance as a cost-saving and environmentally friendly option in place of some wet machining processes. Minimum Quantity Lubricant is actually a misnomer, as it does not refer to an optimal minimal quantity of lubricant. This is a standard term applied to low lubrication flow rate where almost 80% of benefit of flooded lubricant condition may be achieved. Under such condition the flow rate of lubricant is usually kept at few millimeters per hour rather than few liters per hour.